Perancangan Sistem Informasi Perparkiran Universitas Atma Jaya Makassar - Chyan, Phie (TEMATIKA, Journal of Informatics and Information Systems, 2013)
Parking system has been implemented in Universitas Atma Jaya Makassar (UAJM) still not well organized and controlled. In addition to which there were no control data to the vehicle of student, faculty and staff that can be used as an evaluation of parking guard on duty also can not set the vehicle in and out of UAJM the vehicle that incoming outgoing UAJM can not be identified anymore, increasing the likelihood of crime in UAJM. By building computerized parking system application, can help vehicle parking arrangement as well as provide information on the availabil of parking.In this essay, the author uses the Java programming language and database design using software design and UML (Unified Modeling Language).The existence of this research, it can solve the parking problem UAJM in addtion, the result of this study can be uses as a reference in other similiar studies.